Stereotactic Body Radiotherapy Immunological Planning—A Review With a Proposed Theoretical Model - Swamy, Kumara (Frontiers in Oncology, 2022)
In the stereotactic body radiotherapy (SBRT) and immunotherapy era, we are moving toward an “immunological radiation plan”, i.e., radiation scheduling with abscopal effect as a vital endpoint as well. The literature review of part A enumerates the advantages of the intermediate dose of SBRT 6–10 Gy per fraction, appropriate use of dose painting, proper timing with immunotherapy, and the potential of immunoadjuvants to maximize cell kill in the irradiated lesions, found to have improved the abscopal effects. Part B summarizes part A, primarily the findings of animal trials, forming the basis of the tenets of the proposed model given in part C to realize the true abscopal potential of the SBRT tumor cell kill of the index lesions. Part C proposes a theoretical model highlighting tumor vasculature integrity as the central theme for converting “abscopal effect by chance” to “abscopal effect by design” using a harmonized combinatorial approach. The proposed model principally deals with the use of SBRT in strategizing increased cell kill in irradiated index tumors along with immunomodulators as a basis for improving the consistency of the abscopal effect. Included is the possible role of integrating immunotherapy just after SBRT, “cyclical” antiangiogenics, and immunoadjuvants/immune metabolites as abscopal effect enhancers of SBRT tumor cell kill. The proposed model suggests convergence research in adopting existing numerous SBRT abscopal enhancing strategies around the central point of sustained vascular integrity to develop decisive clinical trial protocols in the future.